Lactate, lactate clearance and outcome after cardiac arrest: A post‐hoc analysis of the TTM‐Trial. Issue 10 (21st June 2018) - Düring, J.; Dankiewicz, J.; Cronberg, T.; Hassager, C.; Hovdenes, J.; Kjaergaard, J.; Kuiper, M.; Nielsen, N.; Pellis, T.; Stammet, P.; Vulto, J.; Wanscher, M.; et al.
Abstract : Background: Admission lactate and lactate clearance are implemented for risk stratification in sepsis and trauma. In out‐of‐hospital cardiac arrest, results regarding outcome and lactate are conflicting. Methods: This is a post‐hoc analysis of the Target Temperature Management trial in which 950 unconscious patents after out‐of‐hospital cardiac arrest were randomized to a temperature intervention of 33°C or 36°C. Serial lactate samples during the first 36 hours were collected. Admission lactate, 12‐hour lactate, and the clearance of lactate within 12 hours after admission were analyzed and the association with 30‐day mortality assessed. Results: Samples from 877 patients were analyzed. In univariate logistic regression analysis, the odds ratio for death by day 30 for each mmol/L was 1.12 (1.08‐1.16) for admission lactate, P  < .01, 1.21 (1.12‐1.31) for 12‐hour lactate, P  < .01, and 1.003 (1.00‐1.01) for each percentage point increase in 12‐hour lactate clearance, P  = .03. Only admission lactate and 12‐hour lactate levels remained significant after adjusting for known predictors of outcome. The area under the receiver operating characteristic curve was 0.65 (0.61‐0.69), P  < .001, 0.61 (0.57‐0.65), P  < .001, and 0.53 (0.49‐0.57), P  = .15 for admission lactate, 12‐hour lactate, and 12‐hour lactate clearance, respectively. Conclusions: Admission lactate and 12‐hour lactate values were independently associated with 30‐day mortality after out‐of‐hospital cardiac arrest while 12‐hour lactate clearance was not. The clinical value of lactate as the sole predictor of outcome after out‐of‐hospital cardiac arrest is, however, limited.